Current Practice of Quality Assurance Scheme (QAS) in Different Medical Colleges of Bangladesh (Bangladesh Journal of Medical Education, 2017)
This descriptive cross sectional study was carried out to assess the current status of practice of Quality Assurance Scheme(QAS) in different government and non-government medical colleges of Bangladesh. Principals/academic coordinators and students of all the medical colleges were the study population. Sample size were 13 principals/academic coordinators and 760 MBBS students of different phases. Convenience sampling technique was adopted to conduct the study. Two semi-structured self administered questionnaires one for the students and other for the principal/academic coordinator and one checklist were used to collect data from the respondents . Study revealed that 80.8% medical colleges have complete institutional framework of QAS and 68.1% medical colleges have fully functioning operational framework of QAS. Majority of the medical colleges (53.8%) do not have student representatives in academic coordination committee and only 23% medical colleges collected the phase wise evaluation of the course by the students. More than sixty one percent (61.54%) medical colleges have faculty development and review committee and 76.92% medical colleges have faculty development programme. Provision of exchange review visit by the academic coordinators is absent in 84.61% medical colleges. Almost all the medical colleges (92.31%) prepared and submitted the QAS report to NQAB in the last year. Regarding teaching learning 56.7% students were satisfied/very satisfied. A significant number of students (37.9%) gave negative opinion regarding recognition of students opinion in teaching learning. In the present study it was found that 9.1 % teachers of the selected medical colleges were engaged in research work in last year , 15.5% teachers had publication and 14.8% teachers presented scientific paper at various level in last year.Bangladesh Journal of Medical Education Vol.6(1) 2015: 2-7